The effect of psychological resilience on functional outcomes in post-operative hip fracture patients in a Singapore community hospital. (March 2021) - Tan, Cheryl Yan Fang; Fang, Andrew Hao Sen; Koh, Eileen Yi Ling; Low, Lian Leng
Background: In Singapore, the number of hip fractures per year is projected to increase from 2500 to 9000 by 2050. Psychological factors are increasingly recognised as important predictors of healthy aging. While there are a growing number of studies examining resilience in different populations, there is a paucity of literature examining psychological resilience in individuals with hip fractures. Objectives: We aim to identify the association between high psychological resilience and improved functional outcomes in post-operative hip fracture patients in a Singapore Community Hospital, defined by a Conner-Davidson Resilience Scale 25 (CD-RISC 25) score of 62 and above. Methods: We conducted a pilot prospective cohort study in Bright Vision Community Hospital in Singapore. Post-operative elderly hip fracture patients were invited to participate in the study. Psychological resilience scores were measured on Day 1 of admission using CD-RISC 25. Functional outcomes were then tracked weekly for 21 days while participants underwent rehabilitation using the Modified Barthel Index (MBI). Results: High psychological resilience was found in 52.40% of the post-operative hip fracture participants in this study. Of those participants with high psychological resilience, 55% achieved functional independence ( n = 11), compared with 47.47% of participants with low psychological resilience ( n = 9) – although this result did not achieve statistical significance. Conclusion: One in two post-operative hip fracture patients had high psychological resilience, and our study suggests that patients with high psychological resilience can possibly achieve higher gains in functional scores and achieve functional independence.